2020
DOI: 10.1002/1878-0261.12678
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Calcium Sensor 1 is up‐regulated in response to stress to promote cell survival and motility in cancer cells

Abstract: Changes in intracellular calcium (Ca 2+ ) signaling can modulate cellular machinery required for cancer progression. Neuronal calcium sensor 1 (NCS1) is a ubiquitously expressed Ca 2+ -binding protein that promotes tumor aggressiveness by enhancing cell survival and metastasis. However, the underlying mechanism by which NCS1 contributes to increased tumor aggressiveness has yet to be identified. In this study, we aimed to determine (a) whether NCS1 expression changes in response to external stimuli, (b) the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Previous studies using cellular and animal models have shown that in neurons and cardiomyocytes, NCS-1 exhibits protective activity against various types of stress [35,36,75]. Similar activity on the part of this protein has been demonstrated in breast cancer cells [76]. These observations generally agree with our data obtained using the Y79 model, in that NCS-1 is involved in signaling pathways regulating cell death/survival decisions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using cellular and animal models have shown that in neurons and cardiomyocytes, NCS-1 exhibits protective activity against various types of stress [35,36,75]. Similar activity on the part of this protein has been demonstrated in breast cancer cells [76]. These observations generally agree with our data obtained using the Y79 model, in that NCS-1 is involved in signaling pathways regulating cell death/survival decisions.…”
Section: Discussionsupporting
confidence: 91%
“…Systems biology analysis indicated that NCS1 affects genes related to a broad range of signaling pathways, particularly related to cell morphology and neurodevelopment, which may explain the results we obtained from Golgi‐Cox experiments and stimulated further analysis of developmental databases. A subtle but broad regulatory effect of NCS1 on gene expression was expected—and filtering criteria for the differential gene expression analysis were set accordingly—because NCS1 is not a direct transcription factor but can affect gene expression indirectly through its role in regulating cytosolic and nuclear Ca 2+ signals 9–11,50 . For example, previous studies suggest that NCS1 is involved in the cytosolic activation of Ca 2+ /CaM‐dependent protein kinase CaMKII, which is a major regulator of transcription factors like cAMP response element‐binding protein CREB 21,51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…A subtle but broad regulatory effect of NCS1 on gene expression was expected-and filtering criteria for the differential gene expression analysis were set accordingly-because NCS1 is not a direct transcription factor but can affect gene expression indirectly through its role in regulating cytosolic and nuclear Ca 2+ signals. [9][10][11]50 For example, previous studies suggest that NCS1 is involved in the cytosolic activation of Ca 2+ / CaM-dependent protein kinase CaMKII, which is a major regulator of transcription factors like cAMP response element-binding protein CREB. 21,51,52 Similarly, it has been reported that hippocalcin, another member of the neuronal Ca 2+ sensor family, regulates CREB.…”
Section: Ncs1 As a Modulator Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotype of APOL1Δ and APOL3KO podocytes exhibits striking similarities to that resulting from cancer metastasis, with strong reduction of cellular adherence and increase in cell motility, together with important reduction of the capacity for apoptosis [8]. Accordingly, the APOL3‐controlled NCS‐1 is known to promote motility, metastatic spread and survival of cancer cells [106,107], and the NCS‐1 antagonist CALN‐1 also exhibits relationship with metastatic cell migration [108]. Since in human breast cancer, Golgi PI(4)P is known to regulate cellular adhesion and invasive cell migration [109], the observed reduction of PI(4)P in APOL1Δ and APOL3KO podocytes could be responsible for this metastasis‐like phenotype.…”
Section: Apols and Cancermentioning
confidence: 99%